Find the constant of variation for the relation and use it to write an equation for the statement. Then solve the equation.
![Find the constant of variation for the relation and use it to write an equation for the statement Then solve the equation class=](https://us-static.z-dn.net/files/d6c/2a6679906bc9fc4cbb1ffc40cc7c190b.jpeg)
Answer: option d.
Step-by-step explanation:
Based on the information given, you can write the following expression:
[tex]y=kx[/tex]
Where k is the the constant of variation
If y=2 when x=3, then you can substitute these values into the expression and solve for k:
[tex]k=\frac{2}{3}[/tex]
Substitute k into the expression. Then the equation is:
[tex]y=\frac{2}{3}x[/tex]
Substitute x=1 into the equation. Then, y is:
[tex]y=\frac{2}{3}*1=\frac{2}{3}[/tex]
Answer:
Final answer is choice D. [tex]y=\frac{2}{3}[/tex], [tex]y(1)=\frac{2}{3}[/tex]
Step-by-step explanation:
Given that if y varies directly as x, and y=2 when x=3, then we need to find out y-value when x=1.
We also need to find the constant of variation and the equation.
Since y varies directly as x so we can write equation
y=kx
where k is constant of variation.
Plug given values y=2 and x=3
2=k(3)
[tex]\frac{2}{3} =k[/tex]
Hence constant of variation is [tex]k=\frac{2}{3}[/tex]
Now plug the value of k into formula y=kx
we get required equation as [tex]y=\frac{2}{3}x[/tex]
Now plug the value of x=1 into above formula
[tex]y=\frac{2}{3}x[/tex]
[tex]y=\frac{2}{3}(1)[/tex]
[tex]y=\frac{2}{3}[/tex]
Hence final answer is choice D. [tex]y=\frac{2}{3}[/tex], [tex]y(1)=\frac{2}{3}[/tex]